2024
DOI: 10.1038/s41598-024-57963-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of mechanical thrombectomy in the posterior cerebral circulation—a single center study

Michał Borończyk,
Mikołaj Kuźniak,
Agnieszka Borończyk
et al.

Abstract: Mechanical thrombectomy (MT) is the current standard treatment for strokes in the anterior cerebral circulation (AMT) and has recently been proven to be beneficial in the posterior circulation strokes (PMT). Our study aims to evaluate parameters for favorable outcomes in PMT-patients and to compare the clinical characteristics of individuals who received AMT and PMT. For this purpose, we confronted AMT and PMT-receipients and performed a multivariate regression analysis to assess the influence of factors on fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Conversely, PMT was previously associated with a more intense inflammatory response [ 38 , 39 , 40 ]. Furthermore, in our previous study, we showed that in patients with PMT, both higher CRP levels (OR: 0.995, CI95%: 0.992–0.999) and leukocytosis (OR: 0.974, CI95%: 0.957–0.998) were independent and unfavorable prognostic factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, PMT was previously associated with a more intense inflammatory response [ 38 , 39 , 40 ]. Furthermore, in our previous study, we showed that in patients with PMT, both higher CRP levels (OR: 0.995, CI95%: 0.992–0.999) and leukocytosis (OR: 0.974, CI95%: 0.957–0.998) were independent and unfavorable prognostic factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%